Corporate bodies and guilty minds the failure of corporate criminal liability - Laufer, William S. (Chicago, Ill. ; London : University of Chicago Press, 2006)
In this timely work, William S. Laufer argues that even with recent legal reforms - and those about to be enacted - corporate criminal law continues to be ineffective. This book outlines the many reasons why this is so.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal liability of juristic persons -- United States; Corporation law -- United States -- Criminal provisions; Corporations -- Corrupt practices -- United States; Law; United States of America, USA; Jurisprudence & general issues; Company law; Law of torts, damages & compensation